2010
DOI: 10.1186/1752-1505-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of sexual violence in Eastern Democratic Republic of Congo: reports from survivors presenting to Panzi Hospital in 2006

Abstract: BackgroundDespite the signing of international peace agreements, a deadly war continues in the Democratic Republic of Congo (DRC) and sexual violence is a prominent modus operandi of many military groups operating in the region.MethodsRetrospective cohort study of women who presented to Panzi Hospital in 2006 requesting post-sexual violence care. Data was extracted and analyzed to describe the patterns of sexual violence.ResultsA total of 1,021 medical records were reviewed. A majority of attacks occurred in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 3 publications
8
91
1
Order By: Relevance
“…Since abortion is a criminal offence in the Democratic Republic of Congo, and since adoption is rarely taken as an alternative in Congolese society, most pregnant survivors of sexual violence find themselves responsible for raising a child because of being recognized as a ''rape victim'' and ''mother'' hinder their chances of marrying (Bartels et al 2010). Girls are victims of unwanted pregnancy, because access to pregnancy contraception is unavailable or limited in many places (De Bruyn 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Since abortion is a criminal offence in the Democratic Republic of Congo, and since adoption is rarely taken as an alternative in Congolese society, most pregnant survivors of sexual violence find themselves responsible for raising a child because of being recognized as a ''rape victim'' and ''mother'' hinder their chances of marrying (Bartels et al 2010). Girls are victims of unwanted pregnancy, because access to pregnancy contraception is unavailable or limited in many places (De Bruyn 2000).…”
Section: Introductionmentioning
confidence: 99%
“…85,86 Poverty and desperation may force them to exchange sex for survival, to cross borders, or even for protection. The same conditions that increase the risk of sexual and gender-based violence can also facilitate the spread of HIV, including the use of rape as an instrument of war, genocide, and/or displacement and the breakdown of protective family and community structures.…”
Section: Data Collection and Measurement Challenges And Opportunitiesmentioning
confidence: 99%
“…A study conducted by Bartels et al (2010) found that there are certain patterns to SV in the DRC. Most attacks of SV occur in individual homes, at night, despite the presence of male spouses and/or other male relatives.…”
Section: Sexual Violence and Traumatic Gynaecological Fistulaementioning
confidence: 96%
“…Abortion is illegal in the DRC and there are few family planning clinics. This either results in unsafe abortions or unwanted children, and girls as young as thirteen are left having to care and fend for infants in a society where men typically provide economic support (Bartels et al 2010).…”
Section: Sexual Violence and Traumatic Gynaecological Fistulaementioning
confidence: 99%